Secondary Glaucoma Associated With Orbital Pseudotumor - Prakoeswa, Camilla Amanda; Komaratih, Evelyn; Fatmariyanti, Susy (Journal of Neonatal Surgery, 2025)
Orbital pseudotumor is a non-infectious and benign inflammatory condition of the orbit and the surrounding tissues. This case report aims to emphasize the importance of understanding the cause-effect relationship between orbital inflammation and raised intraocular pressure (IOP). An 18-year-old girl was previously diagnosed with primary angle-closure glaucoma and had a history of twice trabeculectomy surgeries done elsewhere two months before she came to our hospital. She came with left eye pain, eyelid edema, ptosis, conjunctival chemosis, ophthalmoplegia, and elevated IOP despite a positive seidel test for a leaking trabeculectomy bleb. Five months prior to her first surgery she realized an inward squint on her left eye. She also felt joint pain for a year before the ophthalmic symptoms. After comprehensive diagnostics, she was diagnosed with left eye orbital pseudotumor and secondary glaucoma with spondyloarthropathy. Daily 30 mg of oral prednisone was given to reduce the inflammation. After a week, her conditions improved with decreased IOP although there was no additional anti-glaucoma medication. The raised IOP in orbital pseudotumor is often caused by the swelling of orbital tissue and extraocular muscles, that result in choroidal circulation problems from the superior and inferior ophthalmic veins compression. The IOP was greatly reduced once the inflammation was treated Diagnosing orbital pseudotumor may be challenging since it can mimic various conditions. Secondary glaucoma should be acknowledged as a complication in patients with orbital pseudotumor. Once orbital pseudotumor is diagnosed, a systemic steroid should be given to manage the inflammatory conditions as well as resultant glaucoma.